Tendances et évolution des recherches sur la classe inversée en Chine et dans le monde - Hui Zhang; Mengqi Zhang (Nantes Université, 2022)
The flipped classroom, which appeared in the Chinese schools and universities in 2011, was well received there. This paper presents, based on a bibliometric study, the main trends in English-speaking and Chinese-speaking research on the issue, between 2010 and 2020. In this scientific work, the first step is to describe the innovative elements: for as regards tools, use of digital technologies, multimedia supports ; in terms of pedagogy, focus on learners, activity-based learning, cooperation, distinction between low-level tasks, carried out before school time, and high-level tasks, in particular problem-solving, carried out during school time. Some of the research reviewed assesses, using various methods, the effects on learning and academic performance, the building of autonomy, critical thinking skills and teamwork. The paper also shows how scientific work on the question crosses different research disciplines, what are the specificities according to the fields covered, and the main trends of recent developments, especially in China. It pays attention to local characteristics and to the diversification of forms of inversion; it shows the limits of these pedagogies and puts their innovative character into perspective.